Agenda for meeting on 6 July 1938
043-0063-001 SPANISH MEDICAL AID COMMITTEE. A meeting of the Committee will be held at 24, New Oxford St. W.C.1. on Wednesday next, July 6th. at 8.45.p.m. 1. Minutes of last meeting. 2. Matters arising therefrom. 3. Special Correspondence. 4. Report of Organising Sub-Committee. 5. Report of Personnel and Technical Sub-Committee. 6. Financial Report. The Organising Sub-Committee of which you are a member will meet at 7.p.m. on the same day. 292/946/43/63